2016
DOI: 10.1161/jaha.115.002693
|View full text |Cite|
|
Sign up to set email alerts
|

Relations of Central Hemodynamics and Aortic Stiffness with Left Ventricular Structure and Function: The Framingham Heart Study

Abstract: Background--The differing relations of steady and pulsatile components of central hemodynamics and aortic stiffness with cardiac dimensions and function have not been fully elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
68
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 35 publications
11
68
0
2
Order By: Relevance
“…CFPWV was associated with GLS and not GCS, which may indicate that long‐axis function of the LV is more closely linked with global aortic wall stiffness than is short‐axis function. In prior work conducted in this study sample, we have observed that CFPWV is significantly associated with measures of LV diastolic function but not with conventional measures of LV systolic function 48. In light of these prior results, the lack of association of CFPWV with circumferential strain is consistent with the concept that mechanical (ie, non‐hemodynamic) coupling is selectively related to LV function in the long axis.…”
Section: Discussionsupporting
confidence: 77%
“…CFPWV was associated with GLS and not GCS, which may indicate that long‐axis function of the LV is more closely linked with global aortic wall stiffness than is short‐axis function. In prior work conducted in this study sample, we have observed that CFPWV is significantly associated with measures of LV diastolic function but not with conventional measures of LV systolic function 48. In light of these prior results, the lack of association of CFPWV with circumferential strain is consistent with the concept that mechanical (ie, non‐hemodynamic) coupling is selectively related to LV function in the long axis.…”
Section: Discussionsupporting
confidence: 77%
“…The ratio of early transmitral flow velocity (E) and early systolic mitral annulus velocity (e′) was used as an indicator of LV diastolic function. The reproducibility of echocardiographic measurements at FHS has been previously reported 34, 35…”
Section: Methodsmentioning
confidence: 84%
“…E′ was measured using tissue Doppler imaging at the lateral mitral annulus and E was measured using transmitral Doppler flow velocities 34. The ratio of early transmitral flow velocity (E) and early systolic mitral annulus velocity (e′) was used as an indicator of LV diastolic function.…”
Section: Methodsmentioning
confidence: 99%
“…A recent large study of 5799 participants (Framingham Heart Study) also showed significant correlations of cfPWV and central pulse pressure with lateral e′ velocity and E/e′. [8] Borlaug et al [23] performed noninvasive measurement using applanation tonometry in 58 participants, and showed that carotid augementation index and carotid characteristic impedence have an independent association with LV septal e′ velocity. Similarly, our results showed that arterial stiffness measured by baPWV was signficantly correlated with septal e′ velocity and E/e′ in univariate anslyses.…”
Section: Discussionmentioning
confidence: 99%